Forget the Landscape: The Space of Rabbinic and Greco-Roman Mnemonics - Klein, Gil P. (Images, 2017)
Abstract This article investigates the notion of memorization in rabbinic and Roman spatial practices. The Greco-Roman mnemonic technique, in which space was a structuring device for the memorized ideas, words or images, has been extensively studied. Scholars have also demonstrated how such a technique was applied in rabbinic systems of memorization and the arrangement of oral traditions. Nevertheless, very little has been written about the role of mnemonics in the organization of space itself. In the first part of the article I use the comparison between the Corpus Agrimensorum Romanorum (first to fifth centuries CE collection of illuminated manuals of land survey and urban planning) and tractate Eruvin to explore references to cities in the shape of Greek letters, which are almost identical in the two texts. The fact that a list of cities in the shape of letters was used in the Roman corpus as a mnemonic device for the memorization of urban layouts suggests that the rabbis corresponded with such methods in their spatial formulations of the Sabbath Boundary. In the second part of the article I investigate the rabbinic system of forgotten produce (shikheḥah) that maps fields in order to determine which crops were unintentionally left behind by the farmer and consequently belonged to the poor. As I demonstrate, many of the spatial and visual principles applied by the rabbis in this system echo the mnemonic principles described in the Roman work on memorization Rhetorica Ad Herennium. The primary purpose of the article, however, is not merely to illuminate an instance of cultural exchange, but rather to point to the profound link established by mnemonics between space, image and language. The mechanism of organizing words and ideas spatially and visually affected the ways in which space was perceived and was, itself, organized.